ENVIRONMENTAL AUDIT AS AN INSTRUMENT TO PREVENT POLLUTION IN WOOD LAMINATION COMPANIES OF, PUCALLPA 2014 - Castillo Montero, María Micaela (2019)
The central problem is the inadequate prevention of pollution in rolling mills wood Pucallpa. This study aim to determine the incidence of environmental audit as a tool for prevention of environmental pollution in rolling mills wood Pucallpa, this work is justified because: It will allow companies to react to changing needs and preserve, conserve, enhance, restore the environment and natural resources, in order to raise the quality of life of the population, thus adapt to changing social circumstances. As hypothesis is that "There is a significant incidence of environmental auditing as a means of preventing environmental pollution in rolling mills wood Pucallpa". The technique used was through surveys, the research method was inductive, deductive and analytical sample was comprised of 141 companies. As a result must be "There is a significant incidence of environmental auditing as a means of preventing environmental pollution in rolling mills wood Pucallpa". KEYWORDS: Environmental Audit, Environmental Management, Environmental Awareness.